China - Linking Markets for Growth - Garnaut, Ross (ANU Press, 2007)
China's prosperity is at the core of the emerging Platinum Age of global economic growth. Rapid economic growth has been underpinned by expansion in its domestic markets, and the integration of domestic and international markets in goods, services, capital, labour and foreign exchange. Global commodity prices have reached historic highs, while China's capital outflows have helped to hold down interest rates worldwide. Linking markets, both domestic and international, has been key to China's success. In sustaining its strong economic growth, China has become one of the world's most voracious consumers of energy. The challenge now facing the government and people of China is in achieving cooperation with the international community to avert the costs-both economic and environmental-of accelerating energy consumption. China-Linking Markets for Growth gathers together leading scholars on China's economic success and its effect on the world economy into the next few decades.